Work ability of teachers associated with voice disorders, stress, and the indoor environment: A questionnaire study in Finland - Vertanen-Greis Hanna; Löyttyniemi Eliisa; Uitti Jukka; Putus Tuula (Mosby Inc., 2022)
Objectives
The purpose of this study was to determine whether self-reported work ability is associated with voice disorders, stress at work, and the quality of the perceived indoor environment.
Study design
A cross-sectional study.
Methods
We conducted a questionnaire study of 1 198 Finnish teachers utilizing the Work Ability Score.
Results
The Work Ability Score median was 8 (Q1: 7, Q3: 9), and 71% (CI 95% 69%–74%) of the subjects reported that they had good work ability. Female teachers had a significantly lower Work Ability Score than male teachers. The median number of days absent due to sickness during the previous year was 4 (Q1: 2, Q3: 10). Voice disorders (adjusted odds ratio (aOR) 2.44; CI95% 1.73–3.44), stress at work (rather or very much vs. not at all or little; aOR 6.53; CI95% 4.31–9.90), and poor perceived indoor environment quality (aOR 2.63; CI95% 1.86–3.71) were all clear risk factors for the Work Ability Score.
Conclusion
We determined that decreased work ability in teachers is connected to voice disorders, stress at work, and poor perceived indoor environment quality. Thus, in order to better maintain teachers’ work ability, we recommend that special attention should be paid to occupational health care when there are problems in the indoor environment of teachers, and they suffer from voice disorders and stress.